Food supply and poaching limit giraffe abundance in the Serengeti. Issue 3 (18th June 2015) - Strauss, M. K. L.; Kilewo, M.; Rentsch, D.; Packer, C.
Abstract: The iconic giraffe, an ecologically important browser, has shown a substantial decline in numbers across Africa since the 1990s. In Serengeti National Park, Tanzania, giraffes reached densities of 1.5–2.6 individuals km −2 in the 1970s coincident with a pulse of Acacia tree recruitment. However, despite continued increases in woody cover between the 1980s and the 2000s, giraffe recruitment and survival rates have declined and density has dropped to only 0.3–0.4 giraffes km −2 . We used a decision table to investigate how four extrinsic factors may have contributed to these declines: food supply, predation, parasites, and poaching, which have all been previously shown to limit Serengeti ungulate populations. Lower recruitment likely resulted from a reduction in diet quality, owing to the replacement of preferred trees with unpalatable species, while decreased adult survival resulted from illegal harvesting, which appears to have had a greater impact on giraffe populations bordering the western and northern Serengeti. The Serengeti giraffe population will likely persist at low‐to‐moderate densities until palatable tree species regain their former abundance. Leslie matrix models suggest that park managers should meanwhile redouble their efforts to reduce poaching, thereby improving adult survival.